Optical spectral diagnostics of the oxygenation level in periodontal tissues and photodynamic therapy using methylene blue in children with cerebral palsy - Morozova, Natalia S.; Kozlitina, Iuliia A.; Makarov, Vladimir I.; Loschenov, Victor B.; Grinin, Vasiliy M.; Ivanov, Sergey Yu.; Kashtanova, Maria S. (Frontiers in Public Health, 2023)
Dental diseases occur in children with cerebral palsy three times higher than in healthy children. Low values of the unstimulated salivation rate (less than 0.3 ml per minute), pH and buffer capacity, changes in enzyme activity and sialic acid concentration, as well as increased saliva osmolarity and total protein concentration, which indicates impaired hydration, are the factors in the development of a gingiva disease in case of cerebral palsy. Aim: To improve the effectiveness of phototheranostics methods using, namely PDT with simultaneous optical-spectral control, for the treatment of gingivitis in children with complex dental and somatic status (cerebral palsy) Methods: The study involved 15 children (6-18 y.o.) with various forms of cerebral palsy, in particular, spastic diplegia and atonic-astatic form and with gingivitis. The degree of hemoglobin oxygenation was measured in tissues before PDT and on the 12th day. PDT was performed using laser radiation (λ = 660 nm) with a power density of 150 mW/cm2 with a five-minute application of 0.01% MB. The total light dose was 45 ± 15 J/cm2. . For statistical evaluation of the results, a paired Student's t-test was used. Results: The paper presents the results of phototheranostics using methylene blue in children with cerebral palsy. An increase in the level of hemoglobin oxygenation from 50% to 67% (p<0.001) and a decrease in blood volume in the microcirculatory bed of periodontal tissues were shown.